Prevalence and risk factors for HBV and HCV in prisoners in Iran: a national bio‐behavioural surveillance survey in 2015. Issue 6 (25th May 2018) - Moradi, Ghobad; Gouya, Mohammad‐Mehdi; Azimizan Zavareh, Fatemeh; Mohamadi Bolbanabad, Amjad; Darvishi, Sonia; Aghasadeghi, Mohammad Reza; Nabavi, Mahmood; Alasvand, Ramin; Tashakorian, Mehrzad; Nouri, Bijan; Rahmani, Khaled; Molaei, Leila
Summary: Objectives: To provide more accurate estimates of the prevalence of Hepatitis B (HBV) and Hepatitis C (HCV) and their contributing factors among prisoners in Iran. Methods: Cross‐sectional study of 6200 Iranian prisoners in 2015. Data were collected through questionnaires and interviews. HBV infection and HCV exposure status of the participants was determined by HBsAg and HCV antibodies blood tests using enzyme‐linked immunosorbent assay (ELISA). Data were analysed in STATA‐12. Result: Prevalence of HCV exposure was 9.48% (95% CI: 8.73–10.27), and prevalence of HBV was 2.48% (95% CI: 2.07–2.89) in the general prison population. In multivariate analysis, the most important risk factor for HBV was a history of drug use in lifetime (adjusted odds ratio, AOR: 1.8, 95% CI: 1.17–3.02). The main risk factors for HCV exposure were a history of drug use in lifetime (AOR: 4.08, CI: 2.56–6.27), age over 30 (AOR: 2.68, CI: 2.01–3.56), and having tattoos (AOR = 1.67, CI: 1.35–2.07). Conclusion: Although vaccination is used to control HBV among prisoners, prevalence of HCV exposure is alarming in the prison population of Iran, especially among people who inject drugs. Eliminating viral hepatitis in Iran by 2030 requires a national commitment and rapid measures for targeting this high‐risk group. Given the increased efficiency of HCV treatment in recent years, prisons provide an opportunity to access patients for treatment.